SYNTHESIS OF BENZENE-1,2,4-TRIYL TRIS(2-((DIETHYLCARBAMOTHIOYL)THIO) ACETATE) (Scientific journal of the Fergana State University, 2024)
This article examined the reaction product of the chloroacetylation of oxyhydroquinone (1,2,4-trioxybenzene) from triatomic phenols in dimethylformamide (DMFA). Benzene-1,2,4-triyl tris(2-((diethylcarbamothioyl)thio)acetate) was produced as a consequence of the reaction. The obtained compound`s structure was verified using contemporary physico-chemical research techniques.